2023
DOI: 10.1097/mlr.0000000000001833
|View full text |Cite
|
Sign up to set email alerts
|

Management of Neck or Back Pain in Ambulatory Care

Abstract: Background/Objective: In recent years, 2 circumstances have changed provider-patient interactions in ambulatory care: (1) the replacement of virtual for in-person visits and (2) the COVID-19 pandemic. We studied the potential impact of each event on provider practice and patient adherence by comparing the frequency of the association of provider orders, and patient fulfillment of those orders, by visit mode and pandemic period, for incident neck or back pain (NBP) visits in ambulatory care. Methods: Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…In other studies, we found that order likelihood is lower for virtual than for in-person visits. 16,17 In this study, we found that 3 moderators that might influence patient treatment adherence did little to account for fulfillment disparities by visit mode.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…In other studies, we found that order likelihood is lower for virtual than for in-person visits. 16,17 In this study, we found that 3 moderators that might influence patient treatment adherence did little to account for fulfillment disparities by visit mode.…”
Section: Resultsmentioning
confidence: 54%
“…An incident NBP visit was defined as: a completed visit (ie, cancelled appointments and opened but incomplete visits were excluded); with an ICD-10 diagnosis identified as primary or principal; be provided as routine or urgent ambulatory care (defined by the department of service – such as the department of family medicine, general internal medicine, or urgent or after hours care or an equivalent virtual visit program such as KPCO synchronous chats or KPMAS “house calls”), provided to a patient 19 years or older of age, and, with no NBP visit within the prior 180 days 16. An incident UTI visit was similarly defined, except the interval between visits was set at 90 days 17…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The KP research studies also tackle new areas in telemedicine research by comparing the impact of telemedicine and in-person visits on ancillary services utilization, including medication, laboratories, and imaging, for urinary tract infections7 neck and back pain,8 and depression 9. These studies found that although ancillary service orders resulting from telemedicine visits were generally high, orders from telemedicine encounters were not placed as often as in-person encounters for urinary tract infections, 7 neck and back pain, 8 but there were no significant changes in patient fulfillment of ordered antidepressant medications 9. The KP findings highlight the importance of prior use of mail-order pharmacy options in promoting the fulfillment of prescribed medication orders, irrespective of visit mode 10.…”
Section: Commentarymentioning
confidence: 99%